Does Tax Avoidance Affect Company Values in Indonesia in 2020 – 2022? - Lim, Kevin; Vonyka, Vonyka (Institut Bisnis dan Informatika Kesatuan, 2023)
This research aims to prove whether the decreasing trend in tax avoidance can increase company value and vice versa. Company value as a dependent variable is proxied using Tobin’s Q formula, tax avoidance as an independent variable is proxied using the GAAP ETR formula, and firm size as a moderating variable is proxied using the natural logarithm of total assets. The type of data used is secondary archival data in the form of financial report data of non-financial companies for the period 2020 to 2022 that are listed on the Indonesia Stock Exchange. The sample obtained was 705 financial reports and the data was then analyzed using structured equation modeling. The results of the research show that tax avoidance has a significant positive effect on the company value of energy sector companies from 2020 to 2022 at an error rate of 5%, and firm size can moderate tax avoidance so that it has a significant negative effect on the company value of basic material sector companies from 2020 to 2022 at an error rate of 10%.